The Effect of Giving Bay Leaves Boiled Water on Gout in Elderly Women in Bpm Hj.Dermawati Medan - Maulidanita, Riska (Institute Of Computer Science (IOCS), 2024)
Uric acid levels increased or above normal limits can cause the risk of hemodynamic disorders such as cardiovascular disease and the risk of metabolic disorders such as kidney dysfunction. Joints that are often attacked by gout are the thumb joint, ankle joint, wrist, knee and others. According to the World Health Organization (WHO) in 2022 Gout arthritis in every country in the world must have the opportunity to live a long and healthy life, the environment is very influential on our behavior and our exposure to health risks. The purpose of this study was to determine whether there was an effect of bay leaf boiled water on gout in elderly women. The design used is Quasi experimental design (pseudo experimental design) with one group pretest postest design in this study will be carried out initial observations on the frequency of gout before being given bay leaf decoction drinks and after being given bay leaf decoction. The population in this study was 25 elderly women who experienced gout in BPM Hj. Dermawati. Purposive sampling with a sample of 10 people. The tool used for data collection is an observation sheet, with a research time of September 2023.This study shows the results of the shapiro wilk normality which means there is no effect of bay leaf boiled water drink on reducing uric acid in elderly women in Bpm Hj.Dermawati MedanThe conclusion of this study is the influence of the Effect of Giving Bay Leaf Boiled Water.